2017
DOI: 10.3168/jds.2016-11679
|View full text |Cite
|
Sign up to set email alerts
|

Estimating genetic and phenotypic parameters of cellular immune-associated traits in dairy cows

Abstract: Data collected from an experimental Holstein-Friesian research herd were used to determine genetic and phenotypic parameters of innate and adaptive cellular immune-associated traits. Relationships between immune-associated traits and production, health, and fertility traits were also investigated. Repeated blood leukocyte records were analyzed in 546 cows for 9 cellular immune-associated traits, including percent T cell subsets, B cells, NK cells, and granulocytes. Variance components were estimated by univari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 67 publications
0
17
0
2
Order By: Relevance
“…Nevertheless, a combination of different indirect indicators of mastitis could be a more successful predictor of udder health. Thus, alternative traits derived from milk SCC, like the presence of at least one test-day (TD) SCC above specific thresholds in the lactation (Urioste et al 2010;Koeck et al 2012;Bobbo et al 2018), as well as blood serum proteins (Bobbo et al 2017;Cecchinato et al 2018) and cellular immuneassociated traits (Denholm et al 2017), have been explored as novel indicators of animal health. For instance, some of the new alternative SCC traits reported by Bobbo et al (2018) have already been incorporated into an aggregate selection index to reduce mastitis susceptibility in Italian Holsteins (Finocchiaro et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a combination of different indirect indicators of mastitis could be a more successful predictor of udder health. Thus, alternative traits derived from milk SCC, like the presence of at least one test-day (TD) SCC above specific thresholds in the lactation (Urioste et al 2010;Koeck et al 2012;Bobbo et al 2018), as well as blood serum proteins (Bobbo et al 2017;Cecchinato et al 2018) and cellular immuneassociated traits (Denholm et al 2017), have been explored as novel indicators of animal health. For instance, some of the new alternative SCC traits reported by Bobbo et al (2018) have already been incorporated into an aggregate selection index to reduce mastitis susceptibility in Italian Holsteins (Finocchiaro et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in humans and livestock have shown that variation in immune traits is often heritable; that is, a significant proportion of phenotypic variance can be attributed to additive genetic effects [3,8,1115]. Genome-wide association studies (GWAS) in these systems have identified a number of genes of relatively large effect contributing to heritable variation, most notably the major histocompatibility complex (MHC) and cytokine genes [4,5,1619].…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of longitudinal studies in humans have found that high immunological diversity is maintained by high inter-individual variation, but that immune profiles of individuals are stable across longitudinal sampling [4,3840]. Studies in cattle found that cellular based immune traits are highly repeatable, while antibody-based traits were less so [15,41]. Therefore, the ability to dissect the relative contributions of among- and within-individual variation in immune phenotype using longitudinal data collected in natural systems is a crucial step towards our understanding of the evolutionary and ecological causes and consequences of observed variation in immunity in the wild.…”
Section: Introductionmentioning
confidence: 99%
“…Исследования, проведенные в условиях современных молочных комплексов, оснащенных доильным оборудованием «DeLaval» и «Westfalia» показали (Kosyachenko et al, 2016), что сила влияния технологии на пожизненную продуктивность составила 21,1 %, при этом на величину неорганизованных факторов приходилось 48,0 %. Однако коммерциализация молочного скота сопровождается и рядом негативных последствий: ухудшением качества молока, снижением иммунного статуса животных, плодовитости, сокращением периода хозяйственного использования коров в стадах (Goncharenko, 2016;Denholm, et al, 2017;Charfeddine & Pérez-Cabal, 2016). Авторы (Donnik et al, 2010;Weber et al, 2013;Compton et al, 2016;De Vries, 2017) сообщают о том, что короткая длительность хозяйственного использования у высокопродуктивных коров связанна с более высокими обменными процессами в их организме, поскольку в сложных условиях они более склоны к заболеваниям и нарушениям репродуктивной функции, чем животные со средними показателями продуктивности, не исключая при этом влияния генетических факторов (Abdalla et al, 2016;VandeHaar et al, 2016;Tsuruta et al, 2017;Banos et al, 2017).…”
Section: продуктивное долголетие коров голштинской породыunclassified